HAMBATAN KOMUNIKASI DALAM PERKULIAHAN (Studi Kasus Mahasiswa Universitas Islam “45” Bekasi) - Kartini Rosmala D.K. (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
Effective communication is communication in which between the source / communicator and the communicant has the same meaning. However, when communicating, noice occurs frequently. Thus, the shared meaning between communicator and communicant is distracted that leads to miscommunication. This study aims to analyze the noises occur in classroom where students and lecturers interact. The subjects of this study are students of communication department.The result shows that the noise is not only from the channel, as Weaver and Shannon’s Communication Model shown, but also from the internal and external factor of the communicants. The internal factors found in the students such as (1) Drowsiness: lack of sleep / tired from work or other activities (2) State of mood ( boredom, lazyness) (3) Personal problems (family, friends, or tasks), (4) Unorganized schedule, (5) Lack of confidence. As for the external factors come from the environment of the students such as noisy classroom and friends during the lesson